ОСОБЕННОСТИ ПОЗДНЕАРХЕЙСКОЙ ГРАНИТИЗАЦИИ И МИГМАТИТООБРАЗОВАНИЯ В БЕЛОМОРСКОМ ПОЯСЕ - Седова И.С.; Глебовицкий В.А. (My University, 2005)
There are certain regularities in evolution of composition of rocks within series of migmatite- and granite-forming of the Late Archean age developed in conditions of amphibolite facies of moderate-high pressure at the area of Khetolambinsky nappe (Tolstik peninsula and the neighboring islands, Belomorsky belt). At the primary stage, as an effect of addiction of Si and alkalis, metatonalites and basites turn into plagiogneisses, then, at the partial melting, there were formed three generations of migmatite leucosomes, distinguished from plagiogra-nite-gneisses by the greater acidity and the lower maficity. Simultaneously with the third generation, in plagiog-ranitc-gneisses there was development of diatectites with the similar composition. Each group of leucosomes is characterized by individual trends on the diagrams «oxide-silicon», Rb-K, REE-SiO2, and that is estimated as the evidence of impossibility of their forming due to crystallization differentiating of a once arisen melt. It is confirmed also by absence of the sustained regularities of REE contents in the migmatite series. The moderate depletion of leucosomes of the late generations in REE may be described by model of nonequilibrium melting. More essential REE depletion is observed usually in varieties with high SiO2 content, it may be bound with processes of acid leaching. The heightened REE contents in some generations of leucosomes will correspond to the model of equilibrium melting.
Keywords: 552.11+550.42; Докембрий::Архей